Respuesta periodontal a la ubicación de los márgenes de las restauraciones protésicas - Escobar-Guendica, Clara Eugenia; Parra, Carlos Mario; Alvear-Espinal, Fanny Estella; Botero-Zuluaga, Leticia; Villa-Marín, Jorge (Revista Facultad de Odontología Universidad de Antioquia, 2016)
The purpose of this investigation was to study the periodontal tissues response to the crown margin location. Thirty six crowns were made, eleven with a margin at the gingival crest, fourteen at subgingival level, and eleven at supragingival level in ten patients who were in need of crown or bridge work. During two years, measurements of gingival index, plaque index, bleeding scores, sulcus measurements, clinical attachment and gingival retraction were made. During the first year, a strict program of professional care was done every 4 months, and during the second year oral hygiene was only supervised by the investigatores. The result was the presence of very low scores of gingival inflammation for the three different cervical location. The only diference of statistical significance was found in the bleeding scores and in the gingival index, showing that the cervical subgingival location was the most affected. We concluded that the marginal location at the gingival crest and at supragingival level respond in similar form, and they are compatible with periodontal health more than the subgingival location. Key Words: Periodontal response, gingival condition, crown margin location.